The Role of The National Land Agency in Preventing and Setting Land Disputes in Indonesia - Purnama, Dwi; Khasanah, Dian Dewi (Journal of Law, Politic and Humanities, 2024)
Land holds a vital role in Indonesia, yet its management faces complex challenges, including land disputes involving individuals, communities, government, and corporations. This research aims to analyze the role of the National Land Agency (Badan Pertanahan Nasional, BPN) in preventing land disputes in Indonesia and to identify the challenges and obstacles faced in the process of resolving land disputes. This study employs a normative legal research method with a legislative and conceptual approach, examining various primary, secondary, and tertiary legal sources through a literature review. Data analysis is conducted qualitatively using descriptive-analytical methods, involving legal interpretation and evaluation of the effectiveness of BPN's role in preventing and resolving land disputes. The results of the research indicate that the National Land Agency (BPN) plays a crucial role in preventing and resolving land disputes in Indonesia through various programs and strategies but faces complex challenges. BPN implements programs such as systematic land registration, the development of an integrated land information system, and agrarian reform to create better land administration. However, BPN also encounters obstacles such as the complexity of disputes, overlapping authorities, resource limitations, conflicts with customary law, and the politicization of land disputes. The diversity of these issues requires different approaches and often involves various parties with conflicting interests, while BPN must contend with resource constraints and a legal framework that does not fully accommodate the complexity of contemporary land issues.